Chemical & Nano-mechanical Study of Artificial Human Enamel Subsurface Lesions - Al-Obaidi, R. (Sci Rep, 2018)
White lesions represent an early phase of caries formation. 20 human sound premolars were subjected to pH cycling procedure to induce subsurface lesions (SLs) in vitro. In addition, 2 teeth with naturally developed white spot lesions (WSLs) were used as references. All specimens characterized by confocal Raman microscopy being used for the first time in examining white & subsurface lesions and providing a high resolution chemical and morphological map based on phosphate peak intensity alterations at 960 cm(−1). Nanoindentation technique was used to measure Hardness (H) and Young’s modulus (E) of enamel. Phosphate map of examined samples exhibited presence of intact surface layer (ISL) followed by severe depletion in (PO(4)(3−)) peak in the area corresponding to the body of the lesion. In all examined groups, the mechanical properties of enamel were decreased in lesion area and found to be inversely related to penetration depth of indenter owing to enamel hierarchical structure. By combining the above two techniques, we linked mechanical properties of enamel to its chemical composition and ensured that the two methods are highly sensitive to detect small changes in enamel composition. Further work is required to bring these two excellent tools to clinical application to perceive carious lesions at an early stage of development.